Antiulcer secondary metabolites from Elaeocarpus grandis, family Elaeocarpaceae, supported by in silico studies. Issue 57 (21st September 2020) - Mohie El-Dien, Radwa Taher; Maher, Sherif A.; Abdelmohsen, Usama Ramadan; AboulMagd, Asmaa M.; Fouad, Mostafa Ahmed; Kamel, Mohamed Salah
Abstract : Elaeocarpus grandis has a very potent analgesic effect, especially to a δ-opioid receptor, but its antiulcer activity has not yet been validated. Abstract : Elaeocarpus grandis has a very potent analgesic effect, especially to a δ-opioid receptor, but its antiulcer activity has not yet been validated. Therefore, the present study was carried out to evaluate the antiulcer potential of the total methanolic extract and its derived fractions of the aerial parts of the plant using an indomethacin-induced gastric ulcer method. One new compound, grandisine H (1 ), and five known compounds, P -methoxy benzaldehyde, methyl gallate, kaempferol, quercetin and heterophyllin A (2–6 ), were isolated from the ethyl acetate fraction, which was the most potent one with an ulcer index value of 5 ± 1.95 (mm) ** (* P < 0.05, ** P < 0.01) and a preventive index of 92.9%, following a bioassay-guided fractionation. The isolated compounds were subjected to a molecular docking study in an attempt to explain their significant antiulcer potential, and the results revealed that kaempferol and quercetin bind to the active site of the M3 receptor with a strong binding affinity via strong hydrogen bonds of −6.081 kcal mol −1 and −6.013 kcal mol −1, respectively. Also, quercetin and heterophyllin A showed a binding affinity with the gastric proton pump receptor and a strong hydrogen bond interaction with the amino acid active sites in the case of an H2 -modeled receptor. These results clarify the effectiveness and importance of the ethyl acetate fraction as a natural anti-ulcer remedy.